Strategi Pemerintah Desa dalam Pengembangan Objek Wisata di Desa Wisata Tarabunga, Kecamatan Tampahan, Kabupaten Toba - Kerisman Eriyadi; Harisan Boni Firmando; Tio R J Nadeak; Elvri T Simbolon; Sudirman Lase (Lembaga Pengembangan Kinerja Dosen, 2023)
Tarabunga Tourism Village has a variety of great tourism potential that can be developed and introduced such as its beautiful and amazing natural potential. The purpose of this study is to determine the development strategy carried out by the Village Government in increasing the number of tourist visits to Tarabunga Village. (2) To determine the involvement of BUMDES, POKDARWIS, and Youth Youth Organization in the management of tourist attractions, (3) To determine the involvement of community leaders in the development of tourist attractions in Tarabunga Village. This research uses descriptive qualitative methods. Data collection techniques used are (1) data collection through observation, interviews and documentation, (2) data presentation, (3) data reduction, and (4) drawing conclusions. The results of this study are that the Village Government does not only work alone but involves various related parties or stackholders called Penta-helix. The strategies carried out by the Village Government are master plan, environmental management and cleanliness, promotion and marketing, environmental sustainability, human resource development, application of Sapta Pesona, cooperation and partnerships. The conclusion drawn by the author is that Tarabunga Tourism Village has rich natural resource potential. The Government's strategy does not only focus on one point or one tourist attraction, but development is carried out as a whole. One of the major strategies owned by the Village Government is the Master plan on the development of Tarabunga Peak Attraction, In developing the potential of Tarabunga Tourism Village both Natural and Cultural Potential, the village government does not only do it alone but also involves various related parties that can contribute directly or indirectly.